Introduction: Evolving Standards in Juvenile Justice from Gault to Graham and Beyond - Mae C. Quinn (Washington University Journal of Law & Policy, 2012)
This collection of Essays explores the ongoing evolution of juvenile justice standards, sharing important theoretical insights about the current state of the law as well as experience-based lessons from committed juvenile practitioners who confront important youth justice issues in our communities and courts. It is being published in conjunction with Washington University‘s 12th annual Access to Equal Justice Colloquium, which this year sought to bring together stakeholders from the national, state, and local levels to share and build juvenile justice expertise during a day-long conference. Our goal was to consider where we have been, where we are now, and where we might go in the future to ensure the delivery of substantive justice for vulnerable youth, with some emphasis on the particular challenges presented by Missouri‘s juvenile justice system.
Keywords: Juvenile law; Juvenile justice administration